PROFIL USAHA AGROINDUSTRI KERAJINAN TEMPURUNG KELAPA â€œGM ARTâ€ DI KOTA TOMOHON - Oprianto ., Meseang; Agnes E. E. Loho; Grace A.J. Rumagit (Sam Ratulangi University, 2016)
The objective of this research is to determine the profile of entrepreneurs and agroindustry enterprises handicrafts made from coconut shell in Tomohon municipality, and to know benefits achieved in one month. Data collection was conducted for three months, from January 2016 to March 2016. The data obtained are primary data and secondary data. The primary data obtained through interviews to business owners of GM Art in Tomohon. Secondary data were taken from the agencies involved in the research namely Tomohon City Government offices. The results of this study showed that the GM business Art located in Tomohon Tengah sub district, Tomohon municipality began operation in 1999 and began to establish training activities learning - teaching in 2006 until now. Enterprises GM Art operates in the field of small industries that use raw materials of coconut shell and the name of the business owner is Mr Gian Mansa derived from Luwuk Banggai. He has the initiative itself to open a craft business that is made from coconut shell in North Sulawesi, especially in Tomohon Tengah Sub district, Tomohon Municipality, Equipment that is in use Enterprises GM Art at the moment is the use of the machine but with the availability of the engine as an auxiliary key workers business owners have not had those perfect so that business owners create an engineering tool that can create products that are new and can be received by the public. GM Enterprises Art has the profit in January 2016 amounted to Rp. 5.915.392 and uses marketing in form of direct and online marketing.